Immobilization of Trametes versicolor Laccase Enzyme to Cu-silica Aerogel and its Decolorization of Synthetic Dyes - Isik, Semih; Yucel, Sevil; Yuzugullu Karakus, Yonca (SPRINGER, 2026)
Laccase from Trametes versicolor was immobilized on a Cu-silica aerogel carrier with a large surface area (370 m & sup2;/g). Its catalytic efficacy against various synthetic dyes was thoroughly evaluated. Under optimal immobilization conditions (25 degrees C, pH 4.5, 2% glutaraldehyde, 12 mg/g enzyme loading, 4 h), immobilization efficiency and activity retention reached 93%, demonstrating the effectiveness of the immobilization strategy. After 10 reuse cycles, the immobilized enzyme retained 80% of its original activity, indicating high operational durability. Additionally, the immobilized biocatalyst exhibited greater stability across a broader temperature range (up to 60 degrees C) and at pH 4.5 compared to the free enzyme. The kinetic data for 2,6-dimethoxyphenol (2,6-DMP) showed a K-m of 0.20 mM (free enzyme: 0.10 mM) and a V-max of 178 & micro;mol min(-)& sup1; mL(-)& sup1; (free enzyme: 69 & micro;mol min(-)& sup1; mL(-)& sup1;). For ABTS, the immobilized system had a K-m of 0.35 mM (free: 0.20 mM) and a V-max of 278 & micro;mol min(-)& sup1; mL(-)& sup1; (free: 500 & micro;mol min(-)& sup1; mL(-)& sup1;), indicating a change in substrate affinity after immobilization. The enhanced catalytic efficiency of the immobilized enzyme was further confirmed by dye degradation tests, which showed 95% elimination of Methylene Blue within 24 h and complete removal of Coomassie Brilliant Blue G-250 and Congo Red. This performance significantly exceeded that of the free enzyme. Therefore, Cu-silica aerogel-immobilized laccase is a strategically valuable biocatalyst with high catalytic efficiency, strong operational stability, and promising scalability, offering significant potential for industrial wastewater treatment and advanced environmental biotechnology applications.
Keywords: Cu-silica aerogels; Immobilization; Covalent binding; Laccase enzyme; Dyes decolorization; GLUTARALDEHYDE CROSS-LINKING; FUNCTIONALIZED SILICA; GLUCOSE-OXIDASE; PURIFICATION; COPPER; DETOXIFICATION; STABILITY; COMPOSITE; REMOVAL; BIODEGRADATION; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology